Intradural Extramedullary Spinal Sarcoidosis Mimicking Meningioma - Ishiwata, Sho (Case Rep Orthop, 2019)
BACKGROUND: Spinal sarcoidosis is a rare subgroup of neurosarcoidosis. Although most sarcoid lesions develop in the intramedullary compartment, intradural extramedullary (IDEM) spinal sarcoidosis is an extremely rare entity. CASE PRESENTATION: We herein report a case of IDEM spinal sarcoidosis mimicking a meningioma. A 32-year-old man presented to the hospital with clumsy hands and was unable to walk without assistance. Magnetic resonance imaging (MRI) of the cervical spine revealed a dural tail sign that is common in meningiomas. The patient underwent gross total resection. The pathological findings consisted with a sarcoid leision of the spinal cord. The patient's myelopathy recovered after surgery. CONCLUSIONS: Physicians should be alert for the possibility of IDEM sarcoidosis mimicking a meningioma in the differential diagnosis of IDEM spinal cord tumors.